Effects induced by high and low intensity laser plasma on SiC Schottky detectors - Sciuto Antonella; Torrisi Lorenzo; Cannavò Antonino; Mazzillo Massimo; Calcagno Lucia (EPJ Web of Conferences, 2018)
Silicon-Carbide detectors are extensively employed as diagnostic devices in laser-generated plasma, allowing the simultaneous detection of photons, electrons and ions, when used in time-of-flight configuration. The plasma generated by high intensity laser (1016 W/cm2) producing high energy ions was characterized by SiC detector with a continuous front-electrode, and a very thick active depth, while SiC detector with an Interdigit front-electrode was used to measure the low energy ions of plasma generated by low intensity laser (1010 W/cm2). Information about ion energy, number of charge states, plasma temperature can be accurately obtained. However, laser exposure induces the formation of surface and bulk defects whose concentration increases with increasing the time to plasma exposure. The surface defects consist of clusters with a main size of the order of some microns and they modify the diode barrier height and the efficiency of the detector as checked by alpha spectrometry. The bulk defects, due to the energy loss of detected ions, strongly affect the electrical properties of the device, inducing a relevant increase of the leakage (reverse) current and decrease the forward current related to a deactivation of the dopant in the active detector region.